Challenges in the application of didactic-methodical procedures in inclusive teaching - Šarčević Ivić-Hofman, Katarina; Fišer, Zrinka; Hanzec Marković, Ivana (Specijalna edukacija i rehabilitacija, 2026)
Introductions. Numerous factors are associated with the successful implementation of educational inclusion, and educators need to provide adequate support to students with disabilities while dealing with many challenges along the way. Aim. The aim of this research was to determine the relationship between work experience, attitude towards inclusion, perceived institutional support, self-assessed professional competences, job stress, and job satisfaction with the implementation of adequate didactic-methodical procedures in the inclusive work environment. Methodology. The study included 309 primary school teachers from various parts of Croatia who had experience educating students with disabilities, with 181 of them teaching students with disabilities at the time. For the purpose of the research, a questionnaire was designed and used to gather participants’ basic socio-demographic data, their assessment of inclusive educational practices (adjustment of didactic-methodical procedures in the classroom), institutional support, perceived competence for working with students with disabilities, attitudes towards inclusion, their job stress, and job satisfaction. Results. The statistical analysis of the gathered data revealed that the selected variables accounted for 25.4% of the variance in the application of adequate didactic-methodical procedures in inclusive classrooms. Self-assessed professional competence and job satisfaction were identified as significant positive predictors. Although perceived institutional support and attitudes towards inclusion were significantly positively correlated with the use of adequate didactic-methodical procedures, they were not significant predictors in the regression model. Conclusion. Findings of this research make a significant contribution to understanding factors influencing working in an inclusive environment in Croatian schools beyond teachers’ attitudes towards inclusion, which are most frequently researched.